Genere e detenzione. Le aporie costituzionali di fronte a una “doppia reclusione” (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The paper analyses the condition of women detainee in a gender perspective. Starting from the analysis of the principle of equality in Antisubordination dimension and from the constitutional tension regarding prisons and sanctions, the paper focuses on the protection granted to mother detainee, which risks to essentialize the condition of women in prison. By framing these issues, the paper addresses the complex relationship between gender, detention, vulnerability, trying to outline the potential evolution of new form of protection. In that way, the possibility to shape a “dual society”, i.e. a gender sensitive society, may emerge, as to guarantee a gender sensitive detention.
Keywords: Detention; women; gender; vulnerability; antisubordination principle